(untitled) (Journal of history, 2023)
In this article presents an analysis of the works of American scientists telling about the history of Kazakhstan of the Soviet period of the second half of the XX-beginning of the XXI century, the history of the local population, economy, culture, traditions, religious beliefs. Historiography is considered by us as a special historical discipline that studies the history of the accumulation of historical knowledge, the methodology of the development and study of historical thought, the history of the creation of historical works and biographies of scientists, the history of scientific institutions, the organization of historical education and the dissemination of historical knowledge. The main purpose of writing the article was to familiarize researchers with the scientific environment, the modern reading community. The article provides a scientific analysis of the works of European and American researchers who wrote about the culture, traditions, religious beliefs of the Kazakhs in the period from the twentieth to the beginning of the twenty-first century. According to the theory and methodology of scientific research, the methods of historicism, objectivity, historical comparative analysis and historical consistency were mainly used. In the post-war years, Anglo-American Sovietology proved its right to take a worthy place in world historiography, was in demand not only in Western countries, but also in the countries of the former Soviet Union. The greatest accuracy and depth of analysis is noted in the works of Hostler Ch., Zenkovsky S.A., Allworth E.,Tillett L., Rywkin M., Winner T., Symmons-Symonolewicz K., Vucinich W.S., Olcott M. B., McLeish J., Dickens M., Bacon E. E., Fierman W., Tasar E., Rowland M., Rollberg P. At the beginning of writing the article, books and articles by American researchers, including on the history of Kazakhstan, were taken as a basis.